Genitaurinary problems of alcohol-substance dependent women and nursing care - Dişsiz, Melike; Yeşiltepe Oskay, Ümran (Journal of Dependence, 2009)
In the studies performed it is determined that the addiction developed by the drug and stimulating material effect negatively the physical, spiritual, social, reproductive and sexual health of the women. It is informed that the drug and alcohol addiction cause amenorrhea, infertility, menstrual disorder and sexual function disorders in women. It is also informed that the use of alcohol in pregnancy can cause syndromes which put in danger the mother's and the fetus's lives. Alcohol and substance addicted women are more likely to be have risky behaviors, such as use of shared syringes, having more than one sexual partner, unprotected sexual intercourse, and having sexual intercourse for money or other substances or to be a victim of these behaviors. The drug and alcohol addicted women are at risk for sexually transmitted diseases, adolescent pregnancies, undesired or unplanned pregnancies and for verbal, physical, sexual violence. All these risks cause reproductive problems for alcohol and drug addicted women. In the health sector, the nurses who work closely with the public, can play an active role in the determination and resolution of the reproductive problems of the addicted women.
Keywords: Addiction; Alcohol addiction; drug addiction; reproductive health; nursing